2000
DOI: 10.1590/s1020-49892000001100006
|View full text |Cite
|
Sign up to set email alerts
|

Detección de anticuerpos contra Trypanosoma cruzi en Somoto, Nicaragua, mediante ELISA indirecto e IFI en muestras de sangre en papel de filtro

Abstract: We standardized a solid-phase enzyme-linked immunosorbent assay (ELISA) in order to study the presence of Trypanosoma cruzi antibodies in asymptomatic persons who live in an area of Nicaragua endemic for Chagas' disease. The test was standardized to analyze filter-paper blood samples, which are easy to transport. In the first phase of our investigation, ELISA was used to study 18 samples of total serum and 18 eluates of blood from patients with chronic Chagas' disease; 30 samples of serum and 30 eluates of blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
7
0
3
Order By: Relevance
“…However, it is noteworthy that these data differ significantly from PAHO estimates, in the case of Nicaragua representing a four-fold increase. Although data on the prevalence of Chagas disease in Central America is scarce, a prevalence as high as 8,5% was found in a sample taken from patients in the area of Somoto in Nicaragua[ 41 ]. The heterogeneity and smaller size of migrant communities analysed in some studies, especially in the case of countries from Central America, with relatively little representation in European countries, represents a challenge to achieve statistically relevant information.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noteworthy that these data differ significantly from PAHO estimates, in the case of Nicaragua representing a four-fold increase. Although data on the prevalence of Chagas disease in Central America is scarce, a prevalence as high as 8,5% was found in a sample taken from patients in the area of Somoto in Nicaragua[ 41 ]. The heterogeneity and smaller size of migrant communities analysed in some studies, especially in the case of countries from Central America, with relatively little representation in European countries, represents a challenge to achieve statistically relevant information.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of the dry blood spot serological method ( Zicker et al 1990 , Palacios et al. 2000 ) - Blood samples for serological screening were obtained on filter paper (Schleicher & Schuell ® no.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Fifty-six samples were from patients with T. cruzi infection confirmed via conventional serology testing and 19 samples were from noninfected patients. Based on the validation results and from previously published data on the method ( Zicker et al 1990 , Palacios et al 2000) , the following cut off values were chosen for screening with the filter paper method: IHA ≥ 1/8 dilutions, ELISA R ≥ 0.8 (R = optic density of the simple/optic density of the negative control).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…A possible solution for eliminating the cross-reactions is to purify the soluble extract to obtain specific antigens from Leishmania species (Palacios et al 2000). In this sense, some authors have pointed out that the cross-reactions are reduced between Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, some authors have pointed out that the cross-reactions are reduced between Leishmania spp. and T. cruzi when using certain immunogenic proteins such as GP57/51 (Boldano et al 1991) or the glycoprotein of 90 kDa (GP90), which are found in the zymodemes of T. cruzi but which are absent in those of Leishmania and T. rangeli (Palacios et al 2000). The SODe of L. (L.) infantum appears to be another immunogenic protein specific for detecting sera of ailing dogs.…”
Section: Discussionmentioning
confidence: 99%